2022
DOI: 10.17691/stm2022.14.6.01
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Weaving Technologies on the Integral Characteristics of Synthetic Vascular Prostheses

Abstract: The aim of the study is to determine physical and structural properties of woven synthetic prostheses depending on the type of the weave.Materials and Methods. Ten vascular prostheses manufactured at the Science and Technology Park of the BNTU "Polytechnic" (Minsk, Republic of Belarus) have been analyzed. The prostheses differed in the type of weaving, duration and temperature of thermal fixation during crimping. Three samples had a single-layer structure and 7 samples had a double-layer structure. Tests for w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…In this work, only one type of prosthesis was studied. We have previously shown that the mechanical properties of woven grafts largely depend on the weaving technologies [11]. Therefore, we cannot exclude the possibility that changes in the graft structure itself (density of fibers and fiber bundles, type of weaving or knitting, etc.)…”
Section: Study Limitationsmentioning
confidence: 96%
See 1 more Smart Citation
“…In this work, only one type of prosthesis was studied. We have previously shown that the mechanical properties of woven grafts largely depend on the weaving technologies [11]. Therefore, we cannot exclude the possibility that changes in the graft structure itself (density of fibers and fiber bundles, type of weaving or knitting, etc.)…”
Section: Study Limitationsmentioning
confidence: 96%
“…Plain woven fabric is the most popular because it is denser and stronger, less permeable to blood, and less likely to unravel during intraoperative modeling and anastomosis. However, even when using the same plain weaving method, the overall pattern and permeability of the fabric depend on the configuration and density of the fibers in the thread, as well as on the weaving equipment and technique [11]. Knitted prostheses are softer, more flexible, and stretchable compared to woven ones, which, on the one hand, is an advantage, but on the other, often leads to dilatation and aneurysms of the prostheses [8,12].…”
Section: Introductionmentioning
confidence: 99%